Medical Supply Company. Ltd. / Siti Nur Fatihah Mohd Nordin - Mohd Nordin, Siti Nur Fatihah (2022)
The case study that had been done consist of 8 subtopics that are being discussed. The subtopic that had been discussed are the information of the company background, problems faced by the company and the purpose of the study made. SWOT analysis also had been done in this paper to determine every aspect which are the strength, weakness, opportunities and threat regarding to the product. The case study also will be discussing about the problem found in regarding the product and the solution for the problems proposed. The recommendation and improvement that can be made to the product in the company also had been discussed in this paper.